Piper aduncum L. (matico) essential oil in vitro antitumoral effect and oral toxicity in mice - Arroyo, Jorge (2014)
Introduction: Piper aduncum (matìco) is a medicinal plant used for gastrointestinal and genitourinary disorders. Objectives: To determine the in vitro antitumoral effect of Piper aduncum (matico) essential oil on seven human tumoral cell lines and its oral toxicity in mice. Design: Experimental. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Human tumoral cell lines HT-29, H-460, MCF-7, M-14, ME-180, DU-145, K-562; and 3T3 fibroblasts and male 40 days post weaning Balb C/53 mice. Interventions: The cell lines HT-29, H-460, MCF-7, M-14, ME-180, DU-145, K-562, and 3T3 were exposed to four different concentrations of Piper aduncum essential oil, and to different 5-fluorouracil concentrations used as a positive control. Cell lines growth inhibition (IC50) was determined using linear regression analysis and DL50 by the number of deaths with each dose. Main outcome measures: Antitumor effect. Results: Piper aduncum essential oil showed cytotoxic activity at IC50 levels > 250 ug/mL on cell lines M-14 (r = -0.99; p < 0.01), DU-145 (r = -0.99; p < 0.01), ME-180 (r = -0.99; p < 0.01). IC50 was between 20 ug/mL and 250 ug/mL on cell lines H-460(r = -0.99; p < 0.01), MCF-7, (r = -0.99; p < 0.01), K562 (r = -0.99; p < 0.01), HT-29 (r = -0.99; p < 0.01). DL50 was > 2 000 mg/kg. Conclusions: P. aduncum essential oil did not show antitumoral effect on seven human tumoral cell lines and it was non toxic.